Soluble ST2 for Prediction of Heart Failure and Cardiovascular Death in an Elderly, Community‐Dwelling Population. Issue 8 (August 2016) - Parikh, Ravi H.; Seliger, Stephen L.; Christenson, Robert; Gottdiener, John S.; Psaty, Bruce M.; deFilippi, Christopher R.
Abstract : Background: Soluble ST2 (sST2), a marker of myocyte stretch and fibrosis, has prognostic value in many cardiovascular diseases. We hypothesized that sST2 levels are associated with incident heart failure (HF), including subtypes of preserved (HFpEF) and reduced (HFrEF) ejection fraction, and cardiovascular death. Methods and Results: Baseline serum sST2 was measured in 3915 older, community‐dwelling subjects from the Cardiovascular Health Study without prevalent HF. sST2 levels were associated with older age, male sex, black race, traditional cardiovascular risk factors, other biomarkers of inflammation, cardiac stretch, myocardial injury, and fibrosis, and abnormal echocardiographic parameters. In longitudinal analysis, greater sST2 was associated with a higher risk of incident HF and cardiovascular death; however, in multivariate models adjusting for other cardiac risk factors and the cardiac‐specific biomarker, N‐terminal pro–type B natriuretic peptide, these associations were attenuated. In these models, an sST2 level above the US Food and Drug Administration–approved cut‐off value (>35 ng/mL) was significantly associated with incident HF (hazard ratio [HR], 1.20; 95% CI, 1.02–1.43) and cardiovascular death (HR, 1.21; 95% CI, 1.02–1.44), and greater sST2 was continuously associated with cardiovascular death (per 1‐ln increment: HR, 1.24; 95% CI, 1.02–1.50). sST2 was not associated with the HF subtypes of HFpEF and HFrEF in adjusted analysis. Addition of sST2 to existing risk models of HF and cardiovascular death modestly improved discrimination and reclassification into a higher risk. Conclusions: The predictive value of sST2 for HF of all subtypes and cardiovascular death is modest in an elderly population despite strong cross‐sectional associations with risk factors and underlying cardiac pathology.